Characteristics of the use of alternative and complementary treatment in dysmenorrhea in women of fertile age - Díaz-Vélez, Cristian (2021)
Objetive: To describe the characteristics of the use of alternative and complementary treatment in dysmenorrhea in women of childbearing age in a city in northern Peru. The study: Cross-sectional analytical study in women of childbearing age in Mórrope, Lambayeque. Prior training on dysmenorrhea and main variables. 336 women were interviewed in their homes after accepting informed consent. Findings: The age group of 15 to 35 years prevailed in the studied population with 83.92% (n=282), with secondary education 57.14% (n=192), more than 90% had lower/marginal socioeconomic status. Regarding dysmenorrhea, more than 30% were found to have severe/unbearable pain, whose main treatment was MAC with 82.1% (n=220). Plants were the main MAC, only finding an association of MAC use with the religion variable (p=0.023). Conclusions: Women of childbearing age notoriously use CAM, such as phytotherapy, as a treatment for dysmenorrhea despite not finding relief